Peningkatan Pengetahuan Remaja Melalui Games Edukasi tentang Rokok Pada Siswa SMPN 01 Lalonggasumeeto Kabupaten Konawe tahun 2023 - Rosmini; Ruslan Majid; Hartati Bahar (Jurnal Pengabdian Masyarakat (JUDIMAS), 2024)
Cigarettes contain tobacco leaves which are very harmful to health. Currently, cigarettes are found in all circles, including adolescents. This service aims to increase the knowledge of SMPN 01 Lalonggasumeeto students of Konawe Regency about smoking through an educational game created, namely the MANGKOK game. Students who are willing to be respondents are 46 students. The service process is carried out by giving serial numbers to respondents then every time a game will be called 7 respondents who will be asked questions. Education was given when the respondents were in the game arena when each respondent finished answering the questions. Knowledge was measured using pretest and posttest questionnaires and processed using the Epi Info application. The results of the Paired Sample T-Test test showed that there was an increase in knowledge after being given the MANGKOK game to adolescents at SMPN 01 Lalonggasumeeto with a p-value (0.000) < alpha (0.05). From the question and answer session, students were hesitant in answering the questions given. Although there was an increase in knowledge, but for the types of questions about the types of cigarettes, their effects, and how to prevent them, there were still some students who were wrong in answering. This service was carried out for 21 days.